2022
DOI: 10.2903/j.efsa.2022.6978
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of two solvent extracts of rosemary (Rosmarinus officinalis L.) when used as feed additive for cats and dogs (Kemin Nutrisurance Europe SRL)

Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of two rosemary extracts obtained from the ■■■■■ of Rosmarinus officinalis L., as a technological (antioxidant) feed additive for cats and dogs. The two rosemary extracts were obtained through two different solvent extraction methods, acetone and ethanol. The additives were specified to contain carnosic acid and carnosol as the reference antioxidative compounds at a minimum content of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The combination of N. sativa seeds and rosemary leaves can reduce the population of protozoa, methanogen, Fibrobacter succinogenes , and Ruminococcus albus in dorper lambs (Odhaib, Adeyemi, Ahmed et al., 2018). However, the FEEDAP Panel (EFSA Panel on additives, products, or substances used in animal feed) suggested that rosemary additives may be irritating to animal skin and eyes (EFSA Panel on Additives et al., 2022). According to the data from the FEEDAP Panel, the maximum safe dietary concentrations of rosemary additives for dogs and cats are 300 mg/kg (acetone extract) and 50 mg/kg (ethanol extract, EE), respectively.…”
Section: Rosemary As a Functional Food Ingredient In The Food Science...mentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of N. sativa seeds and rosemary leaves can reduce the population of protozoa, methanogen, Fibrobacter succinogenes , and Ruminococcus albus in dorper lambs (Odhaib, Adeyemi, Ahmed et al., 2018). However, the FEEDAP Panel (EFSA Panel on additives, products, or substances used in animal feed) suggested that rosemary additives may be irritating to animal skin and eyes (EFSA Panel on Additives et al., 2022). According to the data from the FEEDAP Panel, the maximum safe dietary concentrations of rosemary additives for dogs and cats are 300 mg/kg (acetone extract) and 50 mg/kg (ethanol extract, EE), respectively.…”
Section: Rosemary As a Functional Food Ingredient In The Food Science...mentioning
confidence: 99%
“…It is a commercially important aromatic evergreen shrub with dark green leaves, pale blue flowers, and upright stems (Figure 1) (Farkhondeh et al., 2019), and it is regionally native to the European countries and the Mediterranean region. Nowadays, it is widely cultivated all over the world as a popular decorative plant (EFSA Panel on Additives et al., 2022) and an economically promising crop (Bourhia et al., 2019), and its main producing countries are Spain, Morocco, and Tunisia (Mwithiga et al., 2022). In particular, rosemary is cultivated in significant amounts in China, India, Algerian, Northern Europe, England, and North America.…”
Section: Introductionmentioning
confidence: 99%